Frequency and Phenotype of Circulating Vα24/Vβ11 Double-Positive Natural Killer T Cells during Hepatitis C Virus Infection - Lucas, Michaela (American Society for Microbiology, 2003)
Natural killer T (NKT) cells are thought to be involved in innate responses against infection. We investigated one specific type of NKT cell, Vα24/Vβ11 double positive, in hepatitis C virus (HCV) infection. Lower frequencies of this population were detected in the blood of HCV PCR-positive patients than in controls. Unlike Vα24/Vβ11 NKT cells found in blood, those in the liver appeared to be recently activated.